19F chemical library and 19F-NMR for a weakly bound complex structure. Issue 9 (4th August 2022) - Shinya, Shoko; Katahira, Ritsuko; Furuita, Kyoko; Sugiki, Toshihiko; Lee, Young-Ho; Hattori, Yoshikazu; Takeshita, Kohei; Nakagawa, Atsushi; Kokago, Aoi; Akagi, Ken-ichi; Oouchi, Muneki; Hayashi, Fumiaki; et al.
Abstract : 19 F-NMR analysis using the optimized 19 F chemical library enables the modeling of the structure of the weakly bound protein–compound complex, overcoming the difficulty in fragment-based drug discovery. Abstract : Fragment-based drug discovery (FBDD), which involves small compounds <300 Da, has been recognized as one of the most powerful tools for drug discovery. In FBDD, the affinity of hit compounds tends to be low, and the analysis of protein–compound interactions becomes difficult. In an effort to overcome such difficulty, we developed a 19 F-NMR screening method optimizing a 19 F chemical library focusing on highly soluble monomeric molecules. Our method was successfully applied to four proteins, including protein kinases and a membrane protein. For FKBP12, hit compounds were carefully validated by protein thermal shift analysis, 1 H– 15 N HSQC NMR spectroscopy, and isothermal titration calorimetry to determine dissociation constants and model complex structures. It should be noted that the 1 H and 19 F saturation transfer difference experiments were crucial to obtaining highly precise model structures. The combination of 19 F-NMR analysis and the optimized 19 F chemical library enables the modeling of the complex structure made up of a weak binder and its target protein.